ABC proteins activity and cytotoxicity in zebrafish hepatocytes exposed to triclosan. (15th February 2021) - Guidony, Nicole Soares; Scaini, João Luís Rheingantz; Oliveira, Matheus William Bandeira; Machado, Karina Santos; Bastos, Cláudio; Escarrone, Ana Laura; Souza, Marta Marques
Abstract: Chemicals such as triclosan are a concern because of their presence on daily products (soap, deodorant, hand sanitizers …), consequently this compound has an ubiquitous presence in the environment. Little is known about the effect of this bactericide on aquatic life. The aim of this study is to analyze triclosan exposure (24 h) to an in vitro model, zebrafish hepatocytes cell line (ZF-L), if it can be cytotoxic (mitochondrial activity, membrane stability and apoptosis) and if can activate ATP-binding cassette (ABC) proteins (activity, expression and protein/compound affinity). Triclosan was cytotoxic to hepatocytes when exposed to concentrations (1–4 mg/L). The results showed impaired mitochondria function, as well, plasma membrane rupture and an increase of apoptotic cells. We observed an ABC proteins activity inhibition in cells exposed to 0.5 and 1 mg/L. When ABCBs and ABCC2 proteins expression were analyzed, there was an increase of protein expression in both ABC proteins families on cells exposed to 1 mg/L of triclosan. On molecular docking results, triclosan and the fluorescent used as substrate (rhodamine) presented high affinity with all ABC proteins family tested, showing a greater affinity with ABCC2. In conclusion, this study showed that triclosan can be cytotoxic to ZF-L. Molecular docking indicated high affinity between triclosan and the tested pumps. Graphical abstract: Image 1 Highlights: Triclosan was cytotoxic to zebrafish hepatocytes (ZF-L). Quantifying apoptotic cells was the most sensitive parameter tested. ATP-binding cassette (ABC) proteins were inhibited by triclosan exposure. Exposure to triclosan increased ABCB/ABCC2 proteins expression. Molecular docking showed affinity between triclosan and ABCBs/ABCC.